Brothers among nations the pursuit of intercultural alliances in early America 1580-1660 - Van Zandt, Cynthia Jean (Oxford University Press, 2008)
This work represents an effort to show how central Native Americans were to the European colonial project by demonstrating that the formation of alliances was the only way for the nascent colonies to succeed.